Analysis of the Effectiveness of Compost-Based Activated Carbon for the Removal of Heavy Metals from Leachate at Piyungan Landfill - Iresha, Fajri Mulya; Alisha, Rania; Melani, Noverli Sukma; Gutama, Hatta (Research and Social Study Institute, 2024)
Leachate from the Final Disposal Site (TPA) in Piyungan, Yogyakarta, is a significant source of potential heavy metal contamination. This represents a serious environmental issue as it can pose a threat to human health and ecosystems. Given its significant negative impact, this study aims to evaluate the efficiency of Compost-Based Activated Carbon (CBAC) as an environmentally friendly alternative solution for reducing heavy metal concentrations in leachate. CBAC is produced through a pyrolysis and chemical activation process using 32% HCl. The study tested the ability of CBAC to adsorb Cr, Cu, and Pb from leachate samples. The results indicate that CBAC exhibits significant adsorption capacity, with the highest removal efficiency recorded for copper (Cu), reaching 52.38% in 20 minutes. The removal efficiencies for chromium (Cr) and lead (Pb) were 17.8% and 12.09%, respectively, although at different optimal times. These differences in efficiency suggest that the characteristics of each heavy metal influence its interaction with CBAC. The findings demonstrate the potential of CBAC as an effective and sustainable alternative in waste management, particularly in reducing heavy metal pollution. This study makes a significant contribution to the development of more environmentally friendly and sustainable waste management technologies, offering an innovative solution to address heavy metal contamination issues at TPA Piyungan and similar sites.